A MORPHONOLOGICAL APPROACH TO CLIPPING IN ENGLISH - Xasanov Maxmudjan Abduraxmanovich (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
This paper investigates clipping—a word-formation process also referred to as truncation or shortening—from a morphonological perspective. It aims to define the phenomenon, clarify its terminology, explore its semantic and stylistic implications, and determine whether it qualifies as a legitimate word-formation device. Emphasis is placed on the phonological patterns of clipping in English, revealing that phonological regularities support its classification within generative morphology. Various types of clipping—back-clipping, fore-clipping, syncope, and median clipping—are examined, and the productivity, lexicalization, and morphosyntactic behavior of clipped forms are analyzed. Results suggest that clipping is a structured, rule-governed process that interacts closely with phonology and morphology.